Promosi Media Sosial Instagram terhadap Minat Beli Konsumen @maliqa.katalog di Jawa Barat - Salsabila, Putri Dewi; Fatihah, Dian Candra (Politeknik Piksi Ganesha Indonesia, 2024)
This study aims to assess the effect of Instagram social media on consumer buying interest who follow the @maliqa.catalog account in West Java during the July-December 2023 period. Quantitative methods are used by collecting data through questionnaires to 37 productive consumers who follow the @maliqa.catalog account. The results showed a correlation coefficient of 0.896, indicating that the influence of Instagram social media on buying interest in @maliqa.catalog is in the medium category. The t hypothesis test shows that t count (6.172) > t table (2.030), indicating a significant influence of Instagram social media on consumer buying interest. The coefficient of determination (R square) of 50.8% indicates that 50.8% of variations in consumer buying interest are influenced by Instagram social media. The obstacles faced by the @maliqa.catalog account are caused by the lack of content updates, resulting in old products being covered by the latest products. The solution provided is to update content regularly to increase consumer attractiveness and buying interest.